An assessment of short-term cattle grazing effects on honeybee forage potential in Mediterranean rangelands - Kaminer A.; Kigel J.; Dag A.; Henkin Z. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Beekeepers in Israel claim that cattle grazing during spring reduces honey production potential as a result of the removal of flowers. We studied the impacts of cattle grazing on honeybee forage during spring in a semi-arid Mediterranean habitat. Cattle was introduced to fenced plots in order to reach the required stoking rates and measurements of floral abundance and honeybee visits were carried out during five surveys. In this study, the impact of cattle grazing on honeybee forage activity appeared to be related to floral abundance and to the blooming periods of specific plant species rather than species richness. Crucifers and woody perennials, mainly Labiatae, seemed to be more attractive to honeybees than most herbaceous annuals. Overall, intensive grazing during the spring flowering season did not seem to suppress the full bloom potential or restrain flower production within local flora. Grazing at moderate to high levels (i.e. 0.4-0.8 cows/ha) may actually support natural honeybee forage by increasing the abundance of some important plant species. However it is recommended to restrict certain areas from grazing to support key species that are restrained by grazing and crucial for honeybee forage at the end of the season.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)